Thirdhand Smoke Exposure Affects Mice Pancreas Microstructure - Eva Rianti Indrasari; Annisa Rahmah Furqaani; Listya Hanum Siswanti; Ihsan Muhammad Nauval; Putra Zam Zam Rachmatullah (Universitas Islam Bandung, 2021)
Cigarette residue toxins can accumulate in the body, including the pancreas, which potentially reduces pancreas function. In addition, the active compounds in cigarettes are reporting to interfere with an elevation of reactive oxygen species, leading to disruption of pancreatic microstructures. Furthermore, pancreatic cell dysfunction is responsible for developing diabetes mellitus disease. The objective of this study was to analyze the effect of thirdhand smoke exposure on mice pancreatic microstructure image. It was an in vivo laboratory experimental study with a completely randomized design at the Medical Biology Laboratory of the Universitas Islam Bandung from November 2020–June 2021. The subjects were 20 adult male mice aged 8–10 weeks, weighing 25–30 grams, in good health condition, and randomly divided into two groups (control group and treatment group exposed to thirdhand cigarette smoke for four weeks). After the completion of the exposure period, pancreatic cells isolation was performing. The parameters observed in this study were the number and diameter islet of Langerhans. Data analysis used the independent t test parametric (α=5%). The results showed that the number and diameter islet of Langerhans in the treated group were significantly lower than the control group (p<0.05). The average number in the control group was 9.40±3.20, while in the treatment group was 4.90±2.74 (28% smaller). The average diameter of control was 225.96±50.15 mm, while treatment was 162±49.68 mm (50% lower). In conclusion, thirdhand smoke exposure alters the pancreas microstructure. The toxic compounds on thirdhand cigarette smoke are involving in generating an elevation of free radical levels, depletion of antioxidants, and alteration of signal transduction resulted in acceleration of apoptosis rate of the islet of Langerhans, especially pancreatic β-cells. PENGARUH PAPARAN ASAP ROKOK TERSIER PADA GAMBARAN MIKROSTRUKTUR PANKREAS MENCITToksik residu rokok dapat terakumulasi pada tubuh, termasuk pankeas sehingga dapat menurunkan fungsi pankreas. Selain itu, senyawa aktif dalam rokok dilaporkan meningkatkan radikal bebas yang menyebabkan kerusakan mikrostruktur pankreas. Selanjutnya, disfungsi sel pankreas meningkatkan risiko diabetes melitus. Penelitian ini bertujuan menganalisis pengaruh asap rokok tersier terhadap gambaran mikrostruktur pankreas mencit. Penelitian ini merupakan penelitian eksperimental laboratorium in vivo dengan rancangan acak lengkap di Laboratorium Biologi Medik Universitas Islam Bandung periode November 2020–Juni 2021. Subjek penelitian adalah 20 mencit jantan dewasa berumur 8–10 minggu, bobot 25–30 gram, kondisi sehat, dan dibagi secara acak menjadi dua kelompok (kelompok kontrol dan kelompok perlakuan yang mendapat paparan asap rokok tersier selama empat minggu). Setelah periode pemberian paparan selesai, dilakukan isolasi sel pankreas. Parameter yang diamati dalam penelitian ini adalah jumlah dan diameter pulau Langerhans (islet of Langerhans). Analisis data menggunakan parametrik independent t test (α=5%). Hasil penelitian menunjukkan bahwa jumlah dan diameter pulau Langerhans pada kelompok perlakuan lebih rendah dibanding dengan kelompok kontrol (p<0,05). Jumlah rerata pada kelompok kontrol adalah 9,40±3,20, sedangkan pada kelompok perlakuan 4,90±2,74 (lebih rendah 28%). Diameter rerata pada kelompok kontrol adalah 225,96±50,19 mm dan kelompok perlakuan 162,89±49.68 mm (lebih rendah 50%). Simpulan, paparan asap rokok tersier dapat memengaruhi gambaran mikrostruktur pankreas. Senyawa toksik pada asap rokok tersier diduga terlibat dalam peningkatan kadar radikal bebas, penurunan kadar antioksidan, dan perubahan transduksi sinyal yang mengakibatkan peningkatan laju apoptosis pulau Langerhans, terutama sel β pankreas.